anonymous
  • anonymous
solve 3x-4y=-4 over x+2y=-8
Mathematics
schrodinger
  • schrodinger
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this
and thousands of other questions

anonymous
  • anonymous
I don't understand what's being asked.
anonymous
  • anonymous
3x-4y=-4 x+2y=-8
anonymous
  • anonymous
there's not enough information being shown

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

shadowfiend
  • shadowfiend
That is enough information. I assume you're trying to solve for x and y.
anonymous
  • anonymous
i agree ^^
shadowfiend
  • shadowfiend
So the first step in these situations is ideally to try to get one of the variables in terms of the other. In this case, we'll try to get \(x\) in terms of \(y\). We'll pick the second equation because it's slightly easier: \[\begin{align} x + 2y &= -8\\ x &= -8 - 2y \end{align}\] So far, so good. We can now plug in for \(x\) in the first equation: \[3(-8 - 2y) - 4y = -4\] Now we can solve for \(y\): \[\begin{align} -24 - 6y - 4y &= -4\\ -24 - 10y &= -4\\ -10y &= -4 + 24 = 20\\ y &= \frac{20}{-10} = -2 \end{align}\] So we now know that \(y = -2\). We can plug \(y\) back into our equation for \(x\) and get \(x\): \[x = -8 - 2y = -8 - 2(-2) = -8 + 4 = -4\] Now we have that \(y = -2\) and \(x = -4\), but, we should plug back into both of the original equations to make sure that our result matches the equations: \[3x - 4y = 3(-4) - 4(-2) = -12 + 8 = -4\] That one matches. \[x + 2y = -4 + 2(-2) = -4 - 4 = -8\] And so does that one. The solution is right! Hope that helps.

Looking for something else?

Not the answer you are looking for? Search for more explanations.